Recent Progress in Developing a LiOH‐Based Reversible Nonaqueous Lithium–Air Battery. Issue 1 (2nd December 2022) - Gao, Zongyan; Temprano, Israel; Lei, Jiang; Tang, Linbin; Li, Junjian; Grey, Clare P.; Liu, Tao
Abstract: The realization of practical nonaqueous lithium–air batteries (LABs) calls for novel strategies to address their numerous theoretical and technical challenges. LiOH formation/decomposition has recently been proposed as a promising alternative route to cycling LABs via Li2 O2 . Herein, the progress in developing LiOH‐based nonaqueous LABs is reviewed. Various catalytic systems, either soluble or solid‐state, that can activate a LiOH‐based electrochemistry are compared in detail, with emphasis in providing an updated understanding of the oxygen reduction and evolution reactions in nonaqueous media. We identify the key factors that can switch the cell chemistry between Li2 O2 and LiOH and highlight the debate around these routes, as well as rationalize potential causes for these opposing opinions. The identities of the reaction intermediates, activity of redox mediators and additives, location of reaction interfaces, causes of parasitic reactions, as well as the effect of CO2 on the LiOH electrochemistry, all play a critical role in altering the relative rates of a series of interconnected reactions and all warrant further investigation. Abstract : The progress in developing LiOH‐based nonaqueous lithium–air batteries is reviewed, with emphasis in providing an updated understanding of the oxygen reduction/evolution reactions during cell operation. Many fundamental questions remain unanswered on the identities of the reaction intermediates, locations of reaction interfaces, causes of parasitic reactions, and the effect of CO2 on the LiOH electrochemistry, which all warrant further investigation.